2020
DOI: 10.7827/turkishstudies.43731
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Pandemic Process in Behavioral Economics: The Impact of Anxiety Level on Socio-Economic Decision-Making Behaviors

Abstract: In December in Wuhan city of China, which has become a global epidemic and the impact of the world's cases of coronavirus as many countries as in Turkey affected deeply in a view of socio-economic. As the pandemic process begins to spread massively, the tendency of individuals to over-interpret the danger and the social, economic and psychological risks created by global anxiety are gradually increasing. This study is based on the level of anxiety that can cause individuals to move away from rationality by ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…Sağlık davranışlarını anlamak ve yönlendirmek için psikolojinin ve sosyal dinamiklerin dikkate alınması, daha etkili ve insan odaklı sağlık politikalarının oluşturulmasına yardımcı olması, sağlıkta davranışsal iktisat konulu çalışmaların artmasını sağlamıştır. Özellikle son zamanlarda COVID-19 gibi bulaşıcı hastalıklarda davranışsal iktisattan yararlanarak (Ağan, 2020;Bicchieri ve diğerleri, 2020;Ferraro ve diğerleri, 2021) insanların karantina, aşılama, sosyal mesafe, maske takma gibi yeni davranışsal kazandırılmasını sağlamada daha da ön plana çıkmıştır. Böylelikle artan yayın sayılarını incelemek ve bu yayınların görsel olarak ağ haritalarını incelemek literatürde ihtiyaç haline gelmiştir.…”
Section: Introductionunclassified
“…Sağlık davranışlarını anlamak ve yönlendirmek için psikolojinin ve sosyal dinamiklerin dikkate alınması, daha etkili ve insan odaklı sağlık politikalarının oluşturulmasına yardımcı olması, sağlıkta davranışsal iktisat konulu çalışmaların artmasını sağlamıştır. Özellikle son zamanlarda COVID-19 gibi bulaşıcı hastalıklarda davranışsal iktisattan yararlanarak (Ağan, 2020;Bicchieri ve diğerleri, 2020;Ferraro ve diğerleri, 2021) insanların karantina, aşılama, sosyal mesafe, maske takma gibi yeni davranışsal kazandırılmasını sağlamada daha da ön plana çıkmıştır. Böylelikle artan yayın sayılarını incelemek ve bu yayınların görsel olarak ağ haritalarını incelemek literatürde ihtiyaç haline gelmiştir.…”
Section: Introductionunclassified
“…The COVID-19 pandemic, which has a high risk with both its contagiousness and lethality, has moved people's fears and concerns about the possibility of contracting the disease themselves or their relatives from the individual level to the social level (Doğan and Düzel, 2020: 750). In addition to these existential concerns, as various studies have shown, in the shadow of the discussions that a deep economic recession will occur on a global scale with the pandemic, it has been observed that individuals fear that there will be negative developments in the markets due to the pandemic and even that they will face unemployment at the end of the process (Ağan, 2020(Ağan, : 1015. The pandemic's catching global organizations that responsible for giving advice to policy makers, multinational companies, nation states and even ordinary people off-guard, have increased the burden of the pandemic on societies (Bozkurt, 2020: 116).…”
Section: Introductionmentioning
confidence: 99%
“…Hem yetişkinler hem de çocuklar üzerinde bu etkilere bakıldığında özellikle ebeveyn olan yetişkinler için bu durumun daha zorlayıcı olduğu söylenebilir. Covid 19 sürecinde işsiz kalma korkusuyla evde yoğun çalışma şartları ebeveynleri oldukça etkilemiştir (Ağan, 2020). Odriozola González ve ark., (2020) yaptığı çalışmada ebeveynlerin süreçte sorumluluklarını aksatmakta, sosyal olarak kendini geri çekme, evlilikte çatışma ve çocuklarıyla ilişkilerinde sorun yaşadıkları belirtilmiştir.…”
Section: Introductionunclassified